2018
DOI: 10.1038/s41419-018-0550-9
|View full text |Cite
|
Sign up to set email alerts
|

KIF4A facilitates cell proliferation via induction of p21-mediated cell cycle progression and promotes metastasis in colorectal cancer

Abstract: Kinesin family member 4A (KIF4A) was found to be implicated in the regulation of chromosome condensation and segregation during mitotic cell division, which is essential for eukaryotic cell proliferation. However, little is known about the role of KIF4A in colorectal carcinoma (CRC). This study explored the biological function of KIF4A in CRC progression and investigated the potential molecular mechanisms involved. Here, we found that KIF4A was remarkably upregulated in primary CRC tissues and cell lines compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 43 publications
5
84
0
Order By: Relevance
“…28 Additionally, KIF4A promotes the proliferation of colorectal cancer by the regulation of p21-mediated cell cycle progression, and they found KIF4A knockdown obviously decreased the expression level of pAKT, and the expression level of MEK and ERK was comparable, suggesting that KIF4A promotes CRC proliferation through PI3K/AKT signaling pathway. 15 Interestingly, we found that KIF4A contributed to cell proliferation of ccRCC in vitro and in mice. Whether KIF4A promotes ccRCC through this signaling pathway also requires further study.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…28 Additionally, KIF4A promotes the proliferation of colorectal cancer by the regulation of p21-mediated cell cycle progression, and they found KIF4A knockdown obviously decreased the expression level of pAKT, and the expression level of MEK and ERK was comparable, suggesting that KIF4A promotes CRC proliferation through PI3K/AKT signaling pathway. 15 Interestingly, we found that KIF4A contributed to cell proliferation of ccRCC in vitro and in mice. Whether KIF4A promotes ccRCC through this signaling pathway also requires further study.…”
Section: Discussionmentioning
confidence: 74%
“…14 In recent years, the key role of KIF4A in cancer development has gradually been revealed. 15 KIF4A is widely expressed in a variety of human tissues. 15 Various studies have reported that KIF4A promoted the progression of several cancers, such as cervical cancer and oral cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, Kinesin-4 family genes could affect tumor biological behavior, such as proliferation, invasion, metastasis, and so on. [22][23][24][25] It is well known that the poor prognosis of tumor depends largely on its malignant behavior. So, we speculated that Kinesin-4 family genes might be associated with pancreatic cancer prognosis.…”
Section: Introductionmentioning
confidence: 99%